RESEARCH ON THE DYNAMIC CHARACTERISTICS OF OFFSHORE WIND TURBINES UNDER SEISMIC INDUCED EMERGENCY SHUTDOWN (MT) - NIU KaiLun; YAN YangTian; LI Chun; LI ZhiHao; XUE ShiCheng (Jixie qiangdu)
In order to study the dynamics of a very large monopile offshore wind turbine under emergency shutdown, the DTU 10 MW monopile offshore wind turbine is used as the research object to establish a turbulent wind-wave-earthquake load multi-physics field model with wind and wave correlation and construction of soil-structure coupling model by p-y curve method, Q-z curve method and Winkler model. The dynamics of the wind turbine under normal operation, shutdown and emergency shutdown were studied. The results show that the wind turbine is most affected by the seismic load under the shutdown condition, and the extreme differences of the forward-backward and lateral displacements of the tower top increase by 249.22% and 1 869.14%, respectively, and the peak shear stress of the support structure increases by 333.33% compared with that without the earthquake. During the emergency shutdown operation, the shear stress of the support structure and the strain energy of the tower were greater than the normal operation at the same time due to the blade pitch effect. The emergency shutdown operation increased the displacement range of the tower top and shifted the vibration center to the direction of turbulent wind flow, and effectively relieved the shear force surge of the support structure and the strain energy gathering in the front and rear of the tower caused by the external load.